Analisis Sentimen Ulasan Produk Layanan Internet di Twitter Menggunakan Naive Bayes Classifier - Permadi, Lintang; Asnawi, Choerun; Bayu Saputra, Andika; Fatimah, Nurul (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2023)
This research aimed to conduct sentiment analysis on user reviews of Indihome, one of Indonesia's leading internet service providers, using data collected from Twitter. With a growing user base of 7 million, Indihome achieved an impressive revenue growth rate of 48% by the end of 2019. To assess user satisfaction, sentiment analysis was performed on tweets containing the keyword